Method for improving the mechanical performance and thermal stability of unsaturated polyester resin/waste‐printed circuit board nonmetals composites via isocyanate chemistry. Issue 31 (19th April 2017) - Hu, Dechao; Jia, Zhixin; Zhong, Bangchao; Lin, Jing; Liu, Maolin; Luo, Yuanfang; Jia, Demin
ABSTRACT: To strengthen the interfacial interactions between waste‐printed circuit board (WPCB) nonmetals and unsaturated polyester resin (UPE) and achieve a high performance in UPE composites, a novel type of polyurethane prepolymer (pre‐PU) with dual functions was prepared by the reaction of isophorone diisocyanate with poly(ethylene glycol). We found that pre‐PU was chemically bonded to the surface of the WPCB nonmetals, and a stronger interaction between the WPCB nonmetals and UPE matrix was formed. The mechanical properties and thermal stability of the UPE/pre‐PU–WPCB nonmetal composites showed remarkable improvements compared with those of the UPE/WPCB nonmetals composites, in particular, the impact toughness, which increased threefold. We envision that this promising modification method will not only open up new opportunities for the preparation of high‐performance plastic composites but also provide a guarantee for the practical industrial application of WPCB nonmetals. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45129. Abstract :